Conditions d'apparition d'une embryogénèse somatique sur des cals issus de la culture de tissus foliaires du chêne vert (Quercus ilex) - Féraud-Keller, C.; ESPAGNAC, H. (Canadian Journal of Botany, 1989)
The proliferation of parenchymatous foliar tissue of Quercus ilex was obtained from current year leaves taken from old trees and cultivated in vitro on modified Murashige and Skoog's medium supplemented with benzylaminopurine (4 mg ∙ L−1) and naphthyl acetic acid (0.5 mg ∙ L−1). Only the fragments cultured in October reacted. The neoformations only appeared on calluses that had not been subcultured for 7 months. Primary nodules arising on these calluses were removed and subcultured on the same medium either in the dark or in the light. In the dark only, they produced secondary nodules, which were the source of somatic embryos both in light and dark. Presently, they seem to regulate their structure in the dark but they do not develop in a way that leads to germination.
doi: 10.1139/b89-139doi: 10.1139/b89-139The following values have no corresponding Zotero field: publisher: NRC Research Press
Keywords: Callus; Quercus ilex; tissue culture

NEOFORMATION OF SOMATIC EMBRYOS-LIKE STRUCTURES FROM CORK-OAK (QUERCUS-SUBER L) TISSUE-CULTURES - ELMAATAOUI, M.; ESPAGNAC, H. (COMPTES RENDUS DE L ACADEMIE DES SCIENCES SERIE III-SCIENCES DE LA VIE-LIFE SCIENCES, 1987)
Embryoid-like formations were induced on cork-oak (Quercus suber L.) calluses grown in vitro on Murashige and Skoog's médium, supplemented with IBA and BAP. Thèse formations rapidly differenciated an apical meristem, flanked with two cotylédons, and a radicular meristem on the opposite end. In most cases embryoids' development stopped there, as if meristems became dormant immediately after their organization. But under certain culture conditions these somatic embryos can produce a great number of secondary embryoids. This multiplication capacity seems to be maintained over generations
The following values have no corresponding Zotero field: pub-location: 127 AVE DE LA REPUBLIQUE, 92120 MONTROUGE, FRANCE publisher: JOHN LIBBEY EUROTEXT LTD